EFFECT OF DIFFERENT STOCKING DENSITIES ON GROWTH AND SURVIVAL OF SEABASS FISH (LATES CALCARIFER) NURSERY PHASE IN LOW SALINITY - Noval, Mochammad; Handajani, Hany; Hariyadi, Hariyadi (University of Muhammadiyah Malang)
Increased production of Seabass fish (Lates calcarifer) influences the stocking density used. The purpose of this study was to determine the growth and survival of Seabass (Lates calcarifer) at different densities of low salinity stocking. The study was conducted in May-June 2019 at the Laboratory of Fisheries, University of Muhammadiyah Malang. The material used in the study of Seabass fish (Lates calcarifer) as many as 550 fish with a size of 7 cm and fish feed in the form of B2 Stella. The method used was experimental with a completely randomized design (CRD) with 4 treatments and 3 replications, namely 1 fish/2 L as control (A); 2 fish/2 L (B); 3 fish/2 L (C); 4 fish/2 L (D). Data analysis used anova (P <0.05) and tested further with the Least Significant Difference Test of 5%. The results showed that treatment B (51 ± 2 fish/2 L) produced a specific growth rate of length and weight, survival rate, efficiency of feed utilization, and feed conversion ratio which was better than treatment A (67 ± 1 fish/2L (control)), C (44 ± 3 fish/2 L and D (38 ± 4 fish/2 L).Keywords: Seabass, Lates calcarifer, stress stocking, recirculation.